EVALUATION OF STRATEGIC MANAGEMENT FIELDS CULTURE, CAPABILITY, INFORMATION AND HUMAN RESOURCES OF YOUTH AND SPORT OFFICES OF WEST AZERBAIJAN PROVINCE - Roba Yadollahzadeh; Mir Mohammad Kashef; Hasan Mohamadzadeh; Mehrdad Hefzollesan (Kharkov National Pedagogical University, 2013)
Management has a significant importance in sport organizations, specially, if it is accompanied with a strategic and program-oriented approach. Now in this progressing and developing world sport is not an exception, and many sport organizations are in rapid progress and in most cases the strategic approach of these organizations is the top priority. This study aims at evaluating the fields of strategic management in West Azarbaijan province offices of sport and youth. The subjects of the study are 47 managers and their assistants of W.Azarbaijan youth and sport offices. The tool of gathering data is a standard questionnaire which is made by Vic Gilgeous (improving strategic concerns).The method of descriptive research is a kind of analysis that, it is performed in a field study. For data analyzing, some parameters of descriptive and inferential statistics such as standard deviation, mean, frequency and some other like one sample t-test were used. The results show that the amount of realization of the culture, information and the strategic management resources in offices of youth and sports of W. Azerbaijan, are not in an appropriate condition (p < 0.05).So according to the results of the study we can deduce that the culture, information and strategic management resources in W. Azerbaijan offices of youth and sports, are significantly different with the society average and these fields need to be improved and strengthened.